An Exploratory Study of Knowledge Sharing on SMEs - Chong, Shiaw Yang (2006)
Managers of organisations recognised the importance of knowledge sharing among employees. Large organisations in particular, have gradually implemented knowledge management initiatives to retain their business competence. However, despites the pricy investment on complex ICT¸ many initiatives have failed to deliver results. Organisations begin to realise that individual’s knowledge sharing behaviour is an important determinant for successful knowledge management. This study examines empirically the social psychological factors that support and inhibit individual’s knowledge sharing behaviour with management staffs of Small Medium Enterprises (SMEs) in Malaysia. SMEs were selected as the research target due to their salient economic importance globally and locally, yet limited research was found in the field of knowledge sharing on them. Quantitative responses were collected from 152 decision makers among Malaysian SMEs. Theory of Reasoned Action (TRA) model was adopted and modified in this study to assess if factors that were found to influence the knowledge sharing behaviour and intention on large organisation in previous studies are applicable to SMEs.